Piezo1 in vascular remodeling of atherosclerosis and pulmonary arterial hypertension: A potential therapeutic target - Xu, Han; He, Yu; Hong, Tianying; Bi, Cong; Li, Jing; Xia, Mingfeng (Frontiers in Cardiovascular Medicine, 2022)
Vascular remodeling (VR) is a structural and functional change of blood vessels to adapt to the changes of internal and external environment. It is one of the common pathological features of many vascular proliferative diseases. The process of VR is mainly manifested in the changes of vascular wall structure and function, including intimal hyperplasia, thickening or thinning of media, fibrosis of adventitia, etc. These changes are also the pathological basis of aging and various cardiovascular diseases. Mechanical force is the basis of cardiovascular biomechanics, and the newly discovered mechanical sensitive ion channel Piezo1 is widely distributed in the whole cardiovascular system. Studies have confirmed that Piezo1, a mechanically sensitive ion channel, plays an important role in cardiovascular remodeling diseases. This article reviews the molecular mechanism of Piezo1 in atherosclerosis, hypertension and pulmonary hypertension, in order to provide a theoretical basis for the further study of vascular remodeling.